Performance of Coconut Waste Interior Panels in Reducing Particulate Matter and Moisture - Wasiska Iyati; Asti Ainun Nabilah; Mochamad Muzaki; Agung Murti Nugroho (DIMENSI: Journal of Architecture and Built Environment, 2026)
Indoor Air Quality (IAQ) is a pressing issue in densely populated and poorly ventilated spaces, where pollutants such as PM2.5, PM10, and excessive humidity contribute to health risks including Sick Building Syndrome (SBS). This study proposes a passive and sustainable solution through Coconut Waste Interior Panels (CWIP), made from a 50:50 mixture of activated coconut charcoal (CCAC) and coconut fiber, packaged in perforated wooden boxes. Experiments were conducted in a 27 m³ enclosed room with four scenarios: with/without CWIP and with/without fan circulation, using mosquito coil smoke as the pollutant source. The results showed a significant improvement in indoor air quality (IAQ), with CWIP reducing PM2.5 from 65.67 µg/m³ to 40.27 µg/m³ and PM10 from 82.73 µg/m³ to 49.93 µg/m³ (p < 0.001) without fan circulation. A moderate decrease was also observed with fan assistance. Humidity decreased significantly under static conditions. These findings highlight CWIP as an effective, electricity-free, and environmentally friendly alternative, supporting waste utilization and sustainable indoor air quality improvement in resource-limited and environmentally conscious settings.